2010
DOI: 10.1071/rd10052
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of chromosomal abnormalities in bovine blastocysts derived from unsorted and sex-sorted spermatozoa

Abstract: The aim of the present study was to examine the incidence of chromosomal abnormalities in bovine blastocysts produced by IVF with unsorted, X-sorted or Y-sorted spermatozoa. In Experiment 1, individual blastocysts were processed to examine the incidence of mixoploidy using fluorescent in situ hybridisation. Overall, 80% (44/55) of blastocysts were mixoploid (10/15, 14/15 and 20/25 for X-sorted, Y-sorted and unsorted spermatozoa, respectively; P > 0.05). However, the prevalence of abnormal XY chromosome complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The importance of sperm volume measurement has been emphasised in other andrological studies for sperm sex selection using flow cytometric procedures (sorting X‐ and Y‐bearing spermatozoa) where the biological variation in DNA content was determinant (Garcia‐Herreros et al ., ; Garner et al ., ). However, the differences between live and dead sperm group related to dimensional parameters are most probably due to other factors, such as osmotic differences after sperm membrane damage, that could change membrane permeability and cellular content in the case of dead spermatozoa, reducing the sperm volume (Blässe et al ., ; Marti et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…The importance of sperm volume measurement has been emphasised in other andrological studies for sperm sex selection using flow cytometric procedures (sorting X‐ and Y‐bearing spermatozoa) where the biological variation in DNA content was determinant (Garcia‐Herreros et al ., ; Garner et al ., ). However, the differences between live and dead sperm group related to dimensional parameters are most probably due to other factors, such as osmotic differences after sperm membrane damage, that could change membrane permeability and cellular content in the case of dead spermatozoa, reducing the sperm volume (Blässe et al ., ; Marti et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, another study found no difference between bovine blastocysts produced by IVF with sex-sorted or non-sorted sperm in the expression of 9 developmentally important genes [8]. Similarly, chromosome alterations could theoretically also contribute to reduced embryo development; however, such alterations caused by sperm sorting were not detected in the resultant embryos in a previous report [33]. Clarification of the exact mechanism by which sperm sorting impairs the developmental competence of fertilized oocytes in occasional cases remains an important task for the future.…”
Section: Discussionmentioning
confidence: 99%
“…In pigs, the frequency of aneuploidy in preimplantation embryos varies from 14.3 to 37.3% based on screening of all chromosomes by comparative genomic hybridization (CGH) [Hornak et al, 2009[Hornak et al, , 2015. In cattle, studies mainly focused on polyploidy and mixoploidy, revealing that mixoploidy occurs in 25-90% of bovine embryos [Viuff et al, 1999;Jakobsen et al, 2006;Garcia-Herreros et al, 2010]. Using FISH, it was estimated that aneuploidy is present in at least 30% of bovine oocytes [Nicodemo et al, 2010] and 27% of porcine oocytes [Vozdová et al, 2001].…”
mentioning
confidence: 99%